American economics - Samuels, Warren J., 1933- (Research in the history of economic thought and methodology ;, 2000)
This newly discovered correspondence from Clark to Giddings covers the entire period from their first acquaintance in 1886 to Giddings' death in 1931. However, the vast majority of nearly 280 letters and notes is concentrated within the years 1886-1895 when the most important development of Clark's economic thought as a theoretical economist was accomplished. During this period Clark achieved the formation of his marginal productivity theory of distribution, and a new theory of capital and interest in particular. This also represents one of the most epoch-making periods of the marginal revolution in the United States, in which Clark was playing a leading role. In this period American modern economics began to be established in the history of economic thought.